2013
DOI: 10.3389/fcimb.2012.00169
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia infection tools—characterization of structure and function of adhesins

Abstract: Among the seventeen species of the Gram-negative genus Yersinia, three have been shown to be virulent and pathogenic to humans and animals—Y. enterocolitica, Y. pseudotuberculosis, and Y. pestis. In order to be so, they are armoured with various factors that help them adhere to tissues and organelles, cross the cellular barrier and escape the immune system during host invasion. The group of proteins that mediate pathogen–host interactions constitute adhesins. Invasin, Ail, YadA, YadB, YadC, Pla, and pH 6 antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 110 publications
(163 reference statements)
0
88
0
10
Order By: Relevance
“…The yadA gene is an adhesion that interacts with the extracellular matrix to promote attachment of Y. pseudotuberculosis and Y. enterocolitica to the host cell [24][25][26]. Invasin is a highly efficient molecule that binds β1-intergrins to facilitate uptake of both Y. pseudotuberculosis and Y. enterocolitica by the host through "outside-in" signaling [26][27][28][29]. Even though Y. pestis lost these conserved factors the bacterium acquired additional virulence factors that contribute heavily to the organism's life cycle.…”
Section: The Genus Yersinia Includes Y Pestis Y Pseudotuberculosismentioning
confidence: 99%
See 2 more Smart Citations
“…The yadA gene is an adhesion that interacts with the extracellular matrix to promote attachment of Y. pseudotuberculosis and Y. enterocolitica to the host cell [24][25][26]. Invasin is a highly efficient molecule that binds β1-intergrins to facilitate uptake of both Y. pseudotuberculosis and Y. enterocolitica by the host through "outside-in" signaling [26][27][28][29]. Even though Y. pestis lost these conserved factors the bacterium acquired additional virulence factors that contribute heavily to the organism's life cycle.…”
Section: The Genus Yersinia Includes Y Pestis Y Pseudotuberculosismentioning
confidence: 99%
“…The zipper mechanism occurs when bacterial proteins bind host membrane proteins creating an internalization signal ("outside-in") that induces the bacteria's uptake [260,261]. An example of this is Invasin, a conserved molecule between Y. pseudotuberculosis and Y. enterocolitica that binds β1 intergrins [26,28,29,262,263]. Through clustering of β1 intergrins on the host cell surface the enteric…”
Section: Aatggtgaaggtcggtgtg Acaagcttcccattctcgg Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been linked to invasion of host immune cells and dissemination by its interaction with CD205 on macrophages [72]. A pla mutant is attenuated in a mammalian host due to both its inability to disseminate from the site of infection and through its uptake by macrophages.…”
Section: Plamentioning
confidence: 99%
“…YadB and YadC have the ability to form oligomers that lead to aggregation and mediate invasion to epithelial cells, although they are not necessary for host cell adherence [72,73]. Studies have shown that when both proteins are mutated, there is a substantial decrease in the ability for the bacteria to invade HeLa cells and type I pneumocytes, but does not affect overall adherence to cells [73].…”
Section: Yadb/cmentioning
confidence: 99%